Study of The Effect of Fatigue Level on Reducing the Injury Level in Netball Players - Immas Aqilla Fadia; Mohd Haidzir Abd Manaf; Ida Hasni binti Shaari (International Journal of Public Health Excellence (IJPHE), 2026)
Athletic performance is often affected by fatigue, which can significantly impact neuromuscular function, power output, and overall movement efficiency. Chronic ankle instability orChronic Ankle Instability (CAI)This is a common condition, particularly among athletes, including netball players. It causes structural and functional impairments, such as ligament laxity and weakened muscle support around the joint.ObjectiveThis study aimed to analyze the effects of a fatigue-inducing protocol on jump height, peak power, peak velocity, and reaction time in netball players. The research method used a quantitative pre-post test design with retrospective data analysis. This study used a fatigue protocol to simulate game-like conditions and analyze performance.Counter Movement Jump(CMJ) before and after fatigue using SPSS software. Paired sample t-tests and correlation analyses were performed to assess performance changes. The results showed that although peak velocity did not show statistically significant changes after fatigue, both peak power and jump height decreased significantly, and fatigue impacted lower limb explosive performance. The difference in jump height with fatigue testing before and after the intervention was statistically significant (p<0.001) indicating a significant change in jump height after the fatigue protocol. Correlation analysis showed that there was no significant relationship between CAI and fatigue-induced performance decline.In conclusion,There is a significant effect of fatigue levels on reducing injury rates in netball players.